Influence of long-term (36 years) tillage practices on soil physical properties in a grain sorghum experiment in Southeast Texas. Issue 2 (28th January 2021) - Govindasamy, Prabhu; Mowrer, Jake; Rajan, Nithya; Provin, Tony; Hons, Frank; Bagavathiannan, Muthukumar
ABSTRACT: Experiments were conducted to evaluate the impact of 36 years of no-tillage (NT), compared to conventional-tillage (CT), on soil physical properties in a continuous grain sorghum experiment. Results revealed that long-term tillage treatments had minimal impact on bulk density (BD), total porosity (TP), air-filled porosity (AFP), water-filled pore space (WFPS), and volumetric water content (Θv). However, water-holding capacity (WHC) was 26% greater in NT, compared to CT. Irrespective of the tillage system, soil physical properties differed across soil depth. The BD was greater at the 0 to 5, and 10 to 20 cm soil depths, compared to the 5 to 10 cm depth; further, BD was positively correlated with Θv ( r = 0.47) and WFPS ( r = 0.49). However, the TP and AFP values were greater (52.4% and 52.2%, respectively) at the 5 to 10 cm depth. Penetration resistance (MI) was maximum (≥ 48.11 J cm –1 ) at the greatest depth tested (60 cm) in both tillage systems. Overall, results indicated that NT had a positive impact on WHC. High WHC associated with long-term NT systems is expected to increase available soil water content, thereby improve productivity, especially under limited moisture environments.